Room temperature modified magnetic particles based dispersive solid-phase extraction for the determination of phthalates and mercury(II) ions in water / Abdulhadi Muftah Faraj Benrabha - Abdulhadi Muftah , Faraj Benrabha (2022)
Sample preparation is one of the important procedures in analytical chemistry. Sample preparation techniques have evolved from macro to micro scale to fulfill the requirement of green analytical chemistry. Magnetic dispersive solid-phase extraction (MDSPE) techniques utilizing magnetic solid-based sorbent for the extraction of organic and inorganic compounds from water is one of the emerging sample preparation techniques. On the other hand, the preparation of magnetic solid sorbents for solid-phase extraction often involved time-consuming complex multistep and high-temperature reactions. In this study, the preparation of magnetic solid sorbents was simplified using a single-step coating and the functionalization of magnetic particles at room temperature. The prepared solid adsorbents were a phenyl functionalized magnetic adsorbent (Fe3O4@SiO2-Ph) and poly (4-vinylphenol) coated magnetic adsorbent (Fe3O4@PVP). The Fe3O4@SiO2-Ph was used to determine phthalate esters (butyl phthalate, butyl benzyl phthalate, di-ethylhexyl phthalate, and di-n-octyl phthalate) in water. Under optimized conditions, this developed magnetic dispersive solid-phase extraction method achieved the pre-concentration factor of 100, low method detection limit (0.62–1.02 μgL-1), and limit of quantitation (1.98–3.25 μgL-1), wide linear dynamic range (0.5–100 μgL-1), with a good coefficient of determination (>0.9980) and good repeatability (relative standard deviation <5%) during the extraction of the selected phthalate esters. The developed method was also successfully applied to analyze the selected phthalate esters in drinking water, mineral water, and surface water from the lake with good extraction efficiency (70–102%) and high precision (≤5%). The Fe3O4@PVP was used for the determination of Hg2+ in water. Under optimized conditions, the developed magnetic dispersive solid-phase extraction method reached a low detection limit (0.01 μgL-1), the limit of quantification (0.04 μgL-1), and a good coefficient of determination, R2 of ~1. This method also showed a good recovery (72-90%), high intra-day and inter-day precision at a concentration ranging from 100 to 2000 μgL-1. This method was also used successfully to determine Hg2+ in drinking water, mineral water, and surface water. In conclusion, this study showed that a more sustainable alternative method could be applied in preparing effective magnetic solid sorbent for MDSPE.